2015
DOI: 10.1590/0103-8478cr20141558
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the wind on water application uniformity of a mechanical lateral move irrigation equipment using rotating plate sprinklers

Abstract: Investigations demonstrate that the wind is the factor that causes the biggest negative influence on water application

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Ribeiro et al (2012), reports that among the climatic factors, the wind was the factor that most influenced the uniformity of water distribution. Faria et al (2016), Justi, Vilas Boas and Sampaio (2010) and Frigo et al (2013) which state that with increasing wind speed, the uniformity of water distribution decreases, made the same report. In a survey for sprinkler irrigation evaluation, Justi, Vilas Boas and Sampaio (2010) concluded that the process capability index was directly proportional to the uniformity of distribution.…”
Section: Descriptive Statistics Of the Datamentioning
confidence: 65%
“…Ribeiro et al (2012), reports that among the climatic factors, the wind was the factor that most influenced the uniformity of water distribution. Faria et al (2016), Justi, Vilas Boas and Sampaio (2010) and Frigo et al (2013) which state that with increasing wind speed, the uniformity of water distribution decreases, made the same report. In a survey for sprinkler irrigation evaluation, Justi, Vilas Boas and Sampaio (2010) concluded that the process capability index was directly proportional to the uniformity of distribution.…”
Section: Descriptive Statistics Of the Datamentioning
confidence: 65%
“…According to the regression equation, a 2.5 m s -1 wind speed led to a water jet length of 14.3 m. Therefore, besides the increase in sprinkler spacing, wind speed also causes reduction in the overlapping of the applied water depths and, consequently, reduction in the irrigation distribution uniformity. Reduced wind speed values are vital to ensure an adequate irrigation efficiency, especially for sprinkler systems, since such variable might result in major impacts on water application and distribution (Keller and Bliesner 1990;Faria et al 2016). A strategy to overcome such problem is the practice of overnight irrigations since it might be a way to reduce the effects of high wind speed.…”
Section: Resultsmentioning
confidence: 99%
“…Particularly for sprinkler systems, the uniformity is related not only to its mechanical aspects (flow rate, operating pressure, spacing, nozzle diameter, etc. ), but also to meteorological conditions, especially wind direction and speed (Keller and Bliesner 1990;Faria et al 2016). Its estimate is frequently evaluated based on the uniformity coefficients.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, u 2 values were low in tests 1, 2, 3, 7, 8, and 9 and high in tests 4, 5, and 6 (Table 3). Low u 2 values are essential for the quality of precipitation tests, especially in sprinkler systems, in which this meteorological variable has a major impact on the application and distribution of water (Faria et al, 2016). According to ASAE (American Society of Agricultural Engineers [ASAE], 2001), the accuracy of this test procedure for the assessment of a linear system and center pivot decreases when wind speed exceeds 1 m s −1 .…”
Section: ∆ S (T) − [Rh × S (T)]mentioning
confidence: 99%